Investigating the Barriers to Technology Adoption in Hotel Sector: The Case of Mashhad/Iran - Momtaheni, Shiva (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Nowadays, tourism and hospitality industry are growing globally; countries around the world capitalizing on tourism and hospitality for economic growth and development. However, tourism sector is also evolving as technological change is compelling industries to adapt to new methods of management and applying technology to overcome the challenges of competition, marketing, and cost reduction. The usage of technology helps to improve the service quality, customer satisfaction and increase revenues. The aim of this study is to explore the level of technology application in accommodation sector in Mashhad/Iran with a focus on five- and four-star hotels. The study is also aimed to explore the challenges that these hotels are experiencing as well as their policies to overcome these challenges. This research is also intended to investigate the barriers to technology adoption, and awareness of the hotel managers of the benefits of innovative ideas. A qualitative method is applied in this research, and data collection completed through an in-depth interview with the managers of the sampled hotels based on semi- structured interview questions. Fourteen general managers in five and four stars hotels were involved in this study. Study revealed that there are various barriers to technology adoption; however, the main barrier is the sanctions that is imposed on Iran. Study also revealed that the managers are eager and aware of benefits of new technology; however, accessing them is expensive and almost impossible. Implications and limitations of the study is also explained.

ÖZ: Günümüzde, dünyadaki ekonomik büyüme ve kalkınma için turizm ve konukseverlikten yararlanan ülkelerde turizm ve konaklama endüstrisi küresel olarak büyümektedir. Bununla birlikte, teknolojik değişim endüstrileri yeni yönetim yöntemlerine adapte olmaya ve rekabet, pazarlama ve maliyet azaltma zorluklarının üstesinden gelmek için teknolojiyi uygulamaya zorladığından turizm sektörü de gelişmekte ve teknoloji kullanımı, hizmet kalitesi ile müşteri memnuniyetini ve gelirleri artırmaya yardımcı olmaktadır. Bu çalışmanın amacı beş ve dört yıldızlı otellere odaklanarak Meşhed, İran'da konaklama sektöründeki teknoloji uygulama düzeyini araştırmaktır. Çalışma aynı zamanda bu otellerin yaşadığı zorlukları ve bu zorlukların üstesinden gelmek için politikalarını ve aynı zamanda teknolojinin benimsenmesinin önündeki engelleri ve otel yöneticilerinin yenilikçi fikirlerin yararları konusundaki farkındalıklarını araştırmayı amaçlamaktadır. Araştırmada nitel bir yöntem uygulanmış ve örneklenen otellerin yöneticileri ile yarı yapılandırılmış görüşme sorularına dayalı derinlemesine görüşme yoluyla veri toplama işlemi tamamlanmıştır. Beş ve dört yıldızlı otellerde 14 genel müdür bu çalışmaya dahil edilmiştir. Araştırma, teknolojinin benimsenmesinde çeşitli engeller olduğunu ortaya koymuştur; ancak asıl engel İran'a uygulanan yaptırımlardır. Çalışma ayrıca yöneticilerin yeni teknolojinin faydaları konusunda istekli ve farkında olduklarını; ancak bunlara erişimin pahalı ve neredeyse imkansız olduğunu bildiğini ortaya koymaktadır. Araştırma sonuçları ve sınırlamaları da çalışma sonunda açıklanmıştır.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Co-Supervisor: Prof. Dr. Habib Alipour, Supervisor: Prof. Dr. Hasan Kılıç
Keywords: Tourism Faculty; Tourism Management; Tourism--Iran; Technology Adoption, Hotel Sector, Barriers, City of Mashhad/ Iran